2016
DOI: 10.1002/term.2208
|View full text |Cite
|
Sign up to set email alerts
|

Improved calvarial bone repair by hASCs engineered with Cre/loxP-based baculovirus conferring prolonged BMP-2 and MiR-148b co-expression

Abstract: Repairing large calvarial bone defects remains a challenging task. Previously, it was discovered that that miR-148b, when acting in concert with bone morphogenetic protein 2 (BMP-2), enhanced the osteogenesis of human adipose-derived stem cells (hASCs) and improved calvarial bone healing in nude mice. However, the molecular target of miR-148b remained elusive. Here it is revealed that miR-148b directly targets NOG, whose gene product (noggin) is an antagonist to BMPs and negatively regulates BMP-induced osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The direct targets of miR148b and miR21 were extracted from microRNA.org, and the relevant genes are summarized in Tables S3 and S4 in the Supporting Information. We observe that NOG, an inhibitor of BMP‐2, is a direct target of miR148b, and SOX2, a pluripotency marker, is a target for miR21 …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The direct targets of miR148b and miR21 were extracted from microRNA.org, and the relevant genes are summarized in Tables S3 and S4 in the Supporting Information. We observe that NOG, an inhibitor of BMP‐2, is a direct target of miR148b, and SOX2, a pluripotency marker, is a target for miR21 …”
Section: Resultsmentioning
confidence: 82%
“…MicroRNA‐148b was studied and identified to upregulate alkaline phosphatase to stimulate osteogenesis activity de novo in hBMSCs and hASCs. Li et al investigated miR‐148b in hASCs and reported noggin (NOG), a well‐known bone morphogenetic protein (BMP) gene repressor, as a direct gene target. miR‐148b initiated downregulation of NOG and promoted osteogenic differentiation through upregulation of BMP expression.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of miR-26a has been shown to increase the expression of bone-related factors (e.g., Runt-related transcription factor 2 (RUNX2), osteocalcin (OCN) and bone morphogenetic protein-2 (BMP-2)), and vascular-related factors (e.g., VEGF and Ang1) [21] and to target the glycogen synthase kinase 3-beta (GSK-3β) gene, which is responsible for augmenting bone mineralization and bone mass [22,23]. Similarly, miR-148b has been identified as a potent bone promoter [24], acting to downregulate the noggin expression, which works as an antagonist of BMPs and is produced by the NOG gene [25]. Liao et al showed that the co-expression of miR-148b and BMP-2 can lead to an enhancement in osteogenesis compared to the separate delivery of miR-148b and BMP-2 [26].…”
Section: Bone Interfering Mirnamentioning
confidence: 99%
“…Scaffolds containing ASCs coexpressing BMP-2/miR-148b were implanted into criticalsize mouse calvarial bone defects and showed accelerated bone healing and remodeling after 12 weeks, filling ≈94% of the bone defect area and ≈89% of the bone defect volume. Following on from this study, Li et al [154] focused on elucidation of the molecular target for 148b as it had not been previously identified. This study revealed miR-148b directly targets NOG, which negatively regulates BMP2-induced osteogenesis and bone formation.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 99%